The Philosophy of Dialogue as One of the Aspects to Sustainable Development - Grochowska, Irena (Problemy Ekorozwoju, 2008)
What we understand today as sustainable development is a mechanism allowing for harmonious coexistence. However, developing individualism and an individual approach regarding one’s own views becomes a habit. It is difficult to accept and love the whole of humanity together with its wretchedness; and it is more difficult to love the world than one’s own mind. This dialogue aims at a better understanding of each person’s own faith. By way of mutual understanding it might be possible to specify possible “spaces” in which we can coexist, and to establish a forum for cooperation. The universe is both a mystery and an insecure environment, and humanity aims to build a permanent and safe bastion within it, by way of harmonious coexistence alongside which sustainable development is used as a tool.